Ancient Rome city planning and administration - Robinson, Olivia F. 1938- (Routledge, 1992)
The population of ancient Rome at its peak exceeded that of any previous western city, or any that came after it until the Industrial Revolution. The requirements for its running--to keep inhabitants fed and provided with water, drainage and entertainment, to enable the people to move about freely and in relative safety, to facilitate a reasonable harmony with their neighbours--meant that a pragmatic system of administrative law was needed. This book describes the legal aspects of urbanism, of the functioning of Rome as a city. O. F. Robinson begins by introducing the purely physical aspect of Rome--its population and boundaries. An overview of town planning is followed by an in-depth treatment of building controls, public works, streets and traffic. The Tiber, the main river in Rome, was central to life in the City. Its bridges and sewers, its employment as a transport system, its relationship to the water supply, and its other uses are discussed in detail. This provides the background for an analysis of public health and safety. Additionally, the book focuses on services such as food distribution, entertainment such as the theatre and gladiatorial games, and the forces of law and order. Ancient Rome: City Planning and Administration is a comprehensive survey of the running of a great city without modern technology. It will be of considerable interest to Roman lawyers, historians and archaeologists, as well as those concerned with current local government.
Keywords: Geschichte Anfänge-500; Geschichte 500 v. Chr.-500; Geschichte Anfänge-600; Geschichte 49 v. Chr.-305; Administration municipale - Rome; Lokaal bestuur; Municipes; Stadsplanning; Stadtplanung; Urbanisme - Italie - Rome; City planning -- Rome; Municipal corporations (Roman law); Municipal government -- Rome; Stadtverwaltung; Rom